„Świadek zeznał, co następuje...” Protokoły przesłuchania polskich pracowników kolei pracujących na stacjach w okolicy obozów akcji „Reinhardt” - Majewska, Justyna (Zagłada Żydów. Studia i Materiały, 2017)
The article presents a selection of immediate post-war testimonies of Polish railway workers, who served at train stations at Bełżec, Sobibór and Treblinka. Testimonies, collected during investigations conducted by Polish authorities regarding the death camps, reviles the level of awareness of Polish witnesses to the crimes conducted at the Operation Reinhardt death camps.